PENERAPAN METODE DOUBLE EXPONENTIAL SMOOTHING UNTUK MERAMALKAN PRODUKSI DAN KONSUMSI DOMESTIK BERAS DI INDONESIA - PRASETIA, PUTRI NUR; TRISKA, ANITA; NAHAR, JULITA (E-Jurnal Matematika; Vol 11 No 3 (2022)DO - 10.24843/MTK.2022.v11.i03.p375, 2022)
Rice is one of the most important commodities in Indonesia  since it is one of  the staple food s . Therefore, it becomes one of  Indonesia n   government concerns by  set ting  a goal of 46,8 million tons of rice supply  in  202 4 . Despite 29,67% of  the  population earn s  their living from agriculture, forestry, and fisherie s , the domestic production of rice could not meet its demand  many  times. Hence,  the forecasting of the  production and domestic consumption of rice is needed to  know whether the domestic production is able to meet the demand. In this study, the rice production and domestic consumption were forecasted using the Double Exponential Smoothing (DES) method. The DES was chosen due to the pattern of the data shows the trends without seasonality. The accuracy of the forecasting was measured by Mean Absolute Percentage Error (MAPE) and Durbin-Watson statistic test. The yielded forecasts showed that the production rate is lower than the domestic consumption’s so that it would not meet the demand. It was concluded that the DES suitable to be used to forecast production and domestic consumption of rice in Indonesia since its MAPE are 6,48% and 5,91%, respectively. Moreover, the Durbin-Watson statistic showed that there was no autocorrelations on the errors of both data.